2016
DOI: 10.1002/we.1968
|View full text |Cite
|
Sign up to set email alerts
|

Wind turbines and seismic hazard: a state-of-the-art review

Abstract: Wind energy is a rapidly growing field of renewable energy and as such, intensive scientific and societal interest has been already attracted. Research on wind turbine structures has been mostly focused on the structural analysis, design and/or assessment of wind turbines mainly against normal (environmental) exposures while, so far, only marginal attention has been spent on considering extreme natural hazards that threat the reliability of the lifetime-oriented wind turbine's performance. Especially, recent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(48 citation statements)
references
References 115 publications
0
44
0
Order By: Relevance
“…In the last decades, with the pressing need for clean, renewable, and sustainable energy, intensive attention has been paid to wind energy harvesting. As wind power generation is regarded as an environment‐friendly way to transform wind energy into electric energy, an extensive number of wind turbine towers, including onshore ones and offshore ones, have been installed worldwide, and many of them are located in seismic active areas . Offshore wind turbine towers are preferable than onshore wind turbine towers, because the former one can produce more electric energy, with less adverse influence on the environment on which human rely for living.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, with the pressing need for clean, renewable, and sustainable energy, intensive attention has been paid to wind energy harvesting. As wind power generation is regarded as an environment‐friendly way to transform wind energy into electric energy, an extensive number of wind turbine towers, including onshore ones and offshore ones, have been installed worldwide, and many of them are located in seismic active areas . Offshore wind turbine towers are preferable than onshore wind turbine towers, because the former one can produce more electric energy, with less adverse influence on the environment on which human rely for living.…”
Section: Introductionmentioning
confidence: 99%
“…It is well understood that earthquake motions in the continental shelf from the coastal land to offshore undersea do great harm to the safety of offshore wind turbines in areas of active seismicity [2,3]. Since earthquakes are unpredictable, offshore wind turbines can be operating under different operation conditions when an earthquake occurs [4,5], resulting in different combinations of seismic load and environmental wind and wave loads acting on the wind turbine supporting structures. These combinations of loads cause different nonlinear dynamic responses for offshore wind turbines, which may exceed limit states of the structure and cause failure in both the power generation system and the supporting foundations.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts to study the seismic dynamic responses [6][7][8][9], structural safety [4,5,[10][11][12] and analytical methods [4,13] of wind turbines have been conducted. Most studies focused on onshore wind turbines, which are shorter in the cantilever length than their offshore counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…A complete recent literature review of the topic by Katsanos et al . concluded that the effects of near‐fault records on wind turbines require further investigation.…”
Section: Introductionmentioning
confidence: 99%